Refining the relationship between psychopathy, aggression, and rule-breaking by gender: A comparison of the triarchic and septarchic models of psychopathy. (February 2022) - Pink, Jennifer; Snowden, Robert J.; Price, Menna J.; Kocsondi, Andrea; Lawrence, Chloe; Stephens, Paige; White, Lauren; Gray, Nicola S.
Abstract: Previous research has established relationships between the triarchic model of psychopathy, defined by the TriPM, and aggression. However, recent research has suggested that the TriPM may be better conceptualised as having seven factors (the septarchic model). In a community sample ( N = 404), we analysed measures of aggression and rule-breaking against the TriPM at the three-factor and seven-factor levels, differentiating by gender. Consistent with the septarchic conceptualisation, some factors under each of the three TriPM domains showed different relationships to aggression. For instance, the septarchic subscale of 'Enjoy Hurting' associated with all measures of aggression while 'Callous' had no or weak relationships. The 'Antisocial' scale was associated with proactive aggression (but not reactive aggression) while the 'Impulsive' scale showed the opposite pattern. Few gender differences emerged in the relationships between psychopathy and gender. Overall, the septarchic model revealed relationships between psychopathy and aggression that are not apparent from the triarchic model and thus, may allow a more refined picture of aggression and psychopathy. Highlights: Unique relationships emerged between 7-factor psychopathy subscales and aggression. Enjoy hurting associated with all types of aggression No or weak associations were found between callous and aggression. There were few gender differences related to psychopathy.